An Exploration of the Artistic Form and Performance Practice of Sichuan Qingyin: A Case Study of Zhai Haitang - Wen, Xin (Pacific International Journal, 2026)
Sichuan Qingyin is a traditional quyi genre renowned for its lyrical beauty, narrative expressiveness, and distinctive regional vocal style. This study investigates the artistic form and performance practice of Sichuan Qingyin through a case study of Zhai Haitang, a representative repertoire that integrates key stylistic features such as tonal precision, melodic ornamentation, and dialectal expression. Focusing on vocal training, dialectal characteristics, ornamentation techniques, and performance aesthetics, the research combines literature review, musical analysis, and practical performance experience to examine how Qingyin singers realize expressive intent while maintaining stylistic authenticity. Particular attention is given to the use of “haha qiang,” sliding tones, and tongue trills, as well as the interplay between melodic line and Sichuan dialect tonal patterns. The study demonstrates that the integration of traditional vocal training with contemporary pedagogical methods can enhance performance quality and preserve the genre’s cultural heritage. By providing detailed analysis of melody, ornamentation, and expressive techniques, this research offers valuable insights for the inheritance, teaching, and contemporary development of Sichuan Qingyin.